2018
DOI: 10.3389/fpls.2018.00726
|View full text |Cite
|
Sign up to set email alerts
|

VvBAP1 Is Involved in Cold Tolerance in Vitis vinifera L.

Abstract: The majority of commercial grape cultivars originate from the European grape. While these cultivars have excellent organoleptic qualities, they suffer from a relatively poor tolerance to the cold experienced during winter, resulting in significant damage to grapevines. Thus, low temperature is one of the bottlenecks that restrict the further growth of the grape industry. Research on the mechanism of cold tolerance in grapes is therefore very important. BON association protein 1 (BAP1) is a recently discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…To reveal the biological functions of VvBAP1 in grapevines, We cloned VvBAP1 from the resistant grapevine cultivar 'F-242'and functionally characterized it as the nearest orthologous to AtBAP1 in our previous reports (Zhang et al, 2014). Then, we found that VvBAP1 was correlated with the cold response process in grapevines, VvBAP1 could regulate the soluble sugar content and enhance antioxidant enzyme activities, thereby promoting the grape cold resistance (Hou et al, 2018). In the research presented here, we showed that the elevated expression of VvBAP1 was higher in the resistant cultivars compare to that from sensitive cultivars under high temperature conditions ( Figure 1A).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…To reveal the biological functions of VvBAP1 in grapevines, We cloned VvBAP1 from the resistant grapevine cultivar 'F-242'and functionally characterized it as the nearest orthologous to AtBAP1 in our previous reports (Zhang et al, 2014). Then, we found that VvBAP1 was correlated with the cold response process in grapevines, VvBAP1 could regulate the soluble sugar content and enhance antioxidant enzyme activities, thereby promoting the grape cold resistance (Hou et al, 2018). In the research presented here, we showed that the elevated expression of VvBAP1 was higher in the resistant cultivars compare to that from sensitive cultivars under high temperature conditions ( Figure 1A).…”
Section: Discussionsupporting
confidence: 49%
“…Whether Ca 2+ regulates the affinity of VvBAP1 binding to its phospholipids substrate and therefore is involved in the heat stress response signaling network, will be necessary to investigate in follow-up experiments. In our previous study, the VvBAP1 promoter has the MBS element binding with the MYB transcription factor (Hou et al, 2018). The MYB family is one of most crucial transcription factor families involved in regulating the physiological process such as development, metabolism, and stress response in plants (Dubos et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to the advancement of high-throughput sequencing technology (Alaimo et al, 2017), a huge number of QTLs underlying important phenotypic traits have been explored, such as the MADs-Box gene VviAGL11 on chromosome 18 which codes seedlessness (Mejia et al, 2011;Royo et al, 2018), VvMybA1 on chromosome 2 that affects grape skin color, and several other traits like berry firmness (Carreño et al, 2014;Correa et al, 2016) and resistance (van Heerden et al, 2014;Pap et al, 2016;Zyprian et al, 2016;Zendler et al, 2017;Hou et al, 2018). However, the highest 4 positive selection signals shared by both table and wine grape, which were chromosome 1: 15,167,366 bp, chromosome 10: 12,113,058 bp, chromosome 13: 13,996,633 bp and chromosome 16, 6,961,106 bp, were not linked to those QTLs.…”
Section: Discussionmentioning
confidence: 99%